Nomadic tribes and clans in the history of the Ulus Dzhuchi – Golden Horde - B. G. Ayagan (Nomadic Civilization: Historical Research, 2023)
The author of this article analyzes one of the most poorly studied problems of world historiography, dedicated to the history of the Golden Horde state. In this case, the author believes that in addition to the established definition of the “Golden Horde”, the name “Ulug (Great) Horde” or “Ulus Jochi” is more applicable, as is generally accepted, for example, in modern Kazakh historiography. Meanwhile, the above definition of the existing state nomadic formation, introduced in the 17th century by Polish and German researchers, in our opinion, somewhat narrows the boundaries of the great state. The relevance of studying this topic is due to the fact that there is still very little literature in modern historiography that studies the status and social organization of tribal associations in the history of the Horde. Often there are facts of underestimation of the contribution of nomads to world history. This omission does not allow scientists to fully explore the role and significance of clans, various tribes and their leaders in conquest campaigns, as well as the management system of acquired territories in a nomadic society, to reveal the features, originality and difference between the so-called “nomadic” empires and the culture of settled communities. This aspect of the study is all the more important, since the state created by Genghis Khan and his descendants contributed to a change in the geopolitical realities of medieval history. And in this, as archival materials show, a significant role was played by various tribes and clans, which later became the basis for the formation of new peoples. The author of the article, having a number of works on this topic, considered it necessary to conduct a brief historiographical analysis on this topic. The works of medieval authors, where the history of Ulug Orda is touched upon in detail, are considered. The study introduces into scientific circulation a number of texts of manuscripts published in the modern period.